Synovial biomarkers in the diagnosis of post-traumatic osteoarthritis following anterior cruciate ligament and meniscus injuries: protocol for a systematic review - Helena Donato; Fernando Fonseca; João Pedro Oliveira; João Castro Mendes; José Casanova; Alexandrina Ferreira Mendes (BMJ Open)
Introduction This review aims to synthesise research evidence regarding biomarkers in the synovial fluid that may predict the risk of post-traumatic osteoarthritis (PTOA) in young adults. Considering the high prevalence of knee joint injuries, particularly among youth sports athletes, this review will focus on anterior cruciate ligament and/or meniscal ruptures. These injuries are highly associated with PTOA, with studies indicating that even with surgical reconstruction, 50%–80% of affected individuals develop knee PTOA within a 10-year follow-up.Methods and analysis The results of this systematic review will be reported in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Diagnostic Test Accuracy guidelines. Comprehensive electronic searches will be conducted across five platforms: four bibliographic databases (PubMed, Cochrane Central Register of Controlled Trials, Web of Science Core Collection and Embase) and ClinicalTrials.gov registry. These searches will use combinations of predefined keywords, such as “knee”, “synovial fluid”, “post-traumatic osteoarthritis”, “anterior cruciate ligament”, “meniscus”, “trauma”, “inflammation” and “biomarker”. We will include randomised clinical trials, non-randomised prospective or retrospective clinical studies, case controls, cohort studies and case series, ranging from database inception to 30 June 2024 and published in English. Two independent reviewers will screen and evaluate the retrieved studies to determine their eligibility. Any reviewer disagreements will be resolved through discussion and consensus or, if necessary, by consultation with a third reviewer. The data will be extracted from the included studies and analysed, with the risk of bias assessed using the Quality Assessment of Diagnostic Accuracy Studies 2 tool. A narrative synthesis will be performed to evaluate the strength and consistency of the findings, considering both the methodological quality of the included studies and the reliability of the results.Ethics and dissemination Ethical approval is not required for this review as it is a secondary study based on public and published data. The findings from this work will be submitted for publication in a peer-reviewed journal and presented at relevant academic conferences. Any amendments to the protocol arising from deviations during the study’s execution will be documented and reported in the final publication.PROSPERO registration number CRD42024534272.